(NwOJNA I MIR(B: [(NrOMAN(B]; (N~ASTX (B3 /s (N~ASTX (B6s - (NtOLSTOJ(B, (NlEW nIKOLAEWI^s ((NmOSKWA(B:s (NhUDOVESTWENNAQ LITERATURA(B,s, 1980)
(Nw KNIGU WHODIT TRETIJ TOM ROMANA (B"(NwOJNA I MIR(B".s
rus
Keywords: (NiSTORI^ESKIJ ROMANs; (NkLASSI^ESKAQ PROZAs